Correlation between the conventional, routine histological grading of transitional cell carcinoma of the urinary bladder and morphometric analysis - Al-Obaidi, Zainab A.J.; Al-Obaidi, Hassanain A.J (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Transitional cell carcinoma of the urinary bladder is one of the important malignancies in both sex groups .It is considered as a heterogenous neoplasm with different biological behavior, in which the majority are early non invasive with tendency for recurrence and some may progress to invasive tumor. An important clinicopathological features are ,the tumor stage and histological grade which are used as prognostic parameters of the tumor and play an important role in therapy. Due to the subjectivity of the histological grading , the reproducibility was low . Many studies showed the value of quantitative analysis of the tumor as an important method in determining the recurrence of the tumor and muscular invasion, some other studies showed the value of nuclear measurement as a prognostic tool for bladder carcinoma. Aim of the study: To evaluate the benefit of nuclear image analysis as an objective method for grading of transitional cell carcinoma of the urinary bladder and compare it with the subjective routine histological grading. Material and method: Sixty two cases of transitional cell carcinoma of the urinary bladder, histologically diagnosed and graded according to WHO grading system ,were selected . In each case 8-10 HPF were examined &10-20consecutive cells were studied, also we measured the largest 10 nuclei for each case separately by a computerized image analysis system at x400 magnification. Nuclear area and roundness were determined. Statistical analysis was performed using the analysis of variance and Tukey’s test (HSD). Results: There was no statistical difference in the mean value of nuclear roundness between the three grades (P<0.05), while there was a statistical difference between grade I&III of their mean nuclear area (MNA) &MNA of the largest 10 nuclei (P<0.05). No such difference was found between grade I&II or grade II&III (P<0.05). Conclusion: Morphometric analysis should be based on the selection of special areas and not by random measurement as done on routine histological grading.